The alternative value of thyroid stimulating hormone instead of thyroglobulin in differentiation of follicular thyroid neoplasm in Hashimoto’s thyroiditis - Liu, Jinyue; Kuang, Jie; Sun, Hanxing; Chen, Lingxie; Li, Qinyu; Zhan, Ling; Hong, Ri; Li, Rui; Yan, Jiqi; Qiu, Weihua; Liu, Zhuoran (Frontiers in Oncology, 2024)
PurposesTo provide novel aspects for the preoperative diagnosis and appropriate differentiation strategies for follicular thyroid carcinoma (FTC) and follicular thyroid adenoma (FTA).MethodsAmong 25,765 cases, a total of 326 patients with follicular thyroid neoplasms between 2013 and 2019 were enrolled. Patient demographics, perioperative parameters, surgical profiles and oncologic outcomes were collected and analyzed.ResultsThere were no significant differences in preoperative ultrasound findings between FTA and FTC patients. The true positive rate (sensitivity) and true negative rate (specificity) of fine needle aspiration (FNA) for FTA patients were 0.6956 and 0.5000, respectively, and those for FTC patients were 0.0714 and 0.9348, respectively. Patients with FTC presented significantly higher serum thyroglobulin (TG) levels than patients with FTA. Preoperative TG level was positively related to tumor invasiveness and recurrence or distant metastases in FTC patients. There were 55 patients with Hashimoto’s thyroiditis (HT), accounting for 16.87% of enrolled patients. HT patients had significantly lower serum TG concentrations than antibody-negative patients. Among HT patients, no significant differences were observed in TG levels between the FTA and FTC groups. Instead, FTA patients had significantly higher serum thyroid stimulating hormone (TSH) levels and lower serum T3 (Triiodothyronine) levels compared to FTC patients. Serum TSH level >1.736U/L was associated with benign follicular neoplasms in HT patients according to the receiver operating characteristic (ROC) curve.ConclusionDistinguishing FTC from FTA remains a challenge for ultrasonography and FNA. Serum TG should be measured as a risk factor of FTC. However, in HT patients, serum TSH levels can serve as a more reliable indicator for differentiating FTC from FTA preoperatively.